Ability, Wages, and Income - Staehle, Hans (The Review of Economics and Statistics, 1943)
REFERRING to Moore's Laws of Wages, Professor Schumpeter wrote in I 9 I 6, great idea of investigating the relationship between wage differences and differences in ability opens a vast perspective. The new trail is steep and stony, but it must be followed.' Little systematic investigation has been undertaken since M\ oore's work was published in I9II. The present paper, first, offers a critical review of the major theories which have been put forth on the relation between people's incomes and their abilities; second, attempts to shed further light on the dependence of labor incomes upon abilities; and, finally, sketches the elements of a theory of the skewness in the distribution of labor incomes.